Learning in the workplace : a toolkit for facilitating learning, and assessment in health, and social care settings - Mulholland, Joan, 1939-; Turnock, Chris (Abingdon, Oxon : Routledge, 2013)
This toolkit is designed for preparing health and social care practitioners for their role in facilitating learning in their workplace. It enables readers to recognise learning opportunities, communicate their professional knowledge, provide students with support, judge performance and co-ordinate student contact with others in the workplace.
Learning and teaching in the workplace -- Supporting learning in the workplace -- Reflection on and in the workplace -- Assessment in the workplace -- Working with others in the workplace -- Diversity in the workplace -- Portfolio completion guidelines.
Authors' names reversed on earlier ed.
Includes bibliographical references and index.
Keywords: Employees -- Coaching of; Occupational training; Organizational learning